COLLABORATIVE GOVERNANCE DALAM PROGRAM KELUARGA BERENCANA DI KABUPATEN KAMPAR TAHUN 2023 - Amalia, Lisa Putri; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Collaborative governance has become an essential need. Involving the government, the private sector, non-governmental organizations, and civil society in the formulation and implementation of family planning policies will ensure a comprehensive and integrated framework. This research has the problem formulation "How is the Collaborative Governance Program for Family Planning (KB) in Kampar Regency in 2023?" This study aims to describe the Collaborative Governance Program for Family Planning (KB) in Kampar Regency in 2023. The research method used in this study is a qualitative approach, the type of research used is descriptive, and the types of data used in this study are primary and secondary data. The location of this research was conducted in Kampar Regency with a focus on the DPPKBP3A Office along with several stakeholders who have an interest in implementing Collaborative Governance in the Family Planning Program. (KB). The data collection technique in this research is through interviews and documentation. The data analysis technique involves collecting data, analyzing, describing the data, and drawing conclusions. The findings in this study are as follows: Initial Conditions (starting condition) include a high rate of unmet need, the involvement of several actors in Collaborative Governance, resource imbalance, Leadership (Facilititative Leadership) with methods such as building trust among stakeholders, fair and inclusive leadership, Institutional Design (institutional Design) with transparency in procedures and policies, collective decision-making, Collaborative Process (Collaborative process) with face-to-face dialogue, building trust, commitment to the process, shared understanding, and collaborative outcomes. Keywords: Collaborative Governance, Initial Conditions, Collaboration, Family Planning